Anti-Diarrheal Studies of Aqueous Leaf Extract of Chrozophora Senegalensis in Albino Rats - AA, Ebbo; A, Bello; YM, Liman (Archives of Clinical and Medical Case Reports, 2019)
Diarrhea has a very high morbidity and mortality, especially in children and in developing countries. Chrozophora senegalensis is used in its management among North-Western Nigeria traditional healers. This claim was scientifically investigated using some diarrhea models. The leaves were also subjected to both phytochemical and proximate analyses, for possible explanations. Phytochemical studies of the leaves revealed the presence of alkaloid (1.20%), tannins (0.92%) and flavonoids (0.029%) while proximate composition showed carbohydrates (73.3%), crude fibre (8.5%), crude protein (6.48%), ash (10.0%), moisture (4.0%) and crude fat (2.0%). The acute oral toxicity studies showed no mortality at 5000 mg/kg body weight. The anti-diarrheal activity of the plant using Activated Charcoal Model showed increase in average latent period and decrease in purging index with increase in dose of the extract using castor oil model. In conclusion, Chrozophora senegalensis could be a potential source of anti-diarrheal dru